Simultaneous Determination of Amlodipine and Aliskren in Tablets by High-Performance Liquid Chromatography - (:unkn) unknown (OXFORD UNIV PRESS INC, 2014)
A new, simple, rapid and specific reversed-phase high-performance liquid chromatography (HPLC) method was developed and validated for the simultaneous determination of amlodipine besylate and aliskiren hemifumarate. The HPLC separation was achieved on an RP-18 column (250 x 4.6 mm) using a mobile phase of triethylamine-orthophosphoric acid buffer (50 mM, pH 3.0), acetonitrile and methanol (50:40:10, v/v/v) at a flow rate of 1 mL/min. The method was validated for specificity, linearity, precision, accuracy and robustness. The degree of linearity of the calibration curves, the percent recovery values of amlodipine and aliskiren and the limits of detection (LOD) and quantification (LOQ) for the HPLC method were determined. The linearity of the method was found to be in the concentration range of 5.0-50.0 mu g/mL for aliskiren hemifumarate and 2.65-26.50 mu g/mL for amlodipine besylate, LOD and LOQ values were 0.51, 0.95, 1.70 and 3.18 mu g/mL for amlodipine besylate and aliskiren hemifumarate. The proposed method was successfully applied to amlodipine besylate and aliskiren hemifumarate in pharmaceutical dosage mixtures without any interference from the excipients. The method was found to be precise, accurate, reproducible and robust. The results agreed with those obtained using the developed reference method.
Keywords: OLMESARTAN MEDOXOMIL; BESYLATE; FORMULATIONS; ASSAY